2014
DOI: 10.1021/es503603w
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Sulfur Tolerance of Nickel-Based Anodes for Oxygen-Ion Conducting Solid Oxide Fuel Cells by Incorporating a Secondary Water Storing Phase

Abstract: In this work, a Ni+BaZr(0.4)Ce(0.4)Y(0.2)O(3-δ) (Ni+BZCY) anode with high water storage capability is used to increase the sulfur tolerance of nickel electrocatalysts for solid oxide fuel cells (SOFCs) with an oxygen-ion conducting Sm(0.2)Ce(0.8)O(1.9) (SDC) electrolyte. Attractive power outputs are still obtained for the cell with a Ni+BZCY anode that operates on hydrogen fuels containing 100-1000 ppm of H2S, while for a similar cell with a Ni+SDC anode, it displays a much reduced performance by introducing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…In addition to the modification of surface adsorption properties of Ni, significant sulfur tolerance resistance can be obtained by modifying the ionic oxide support e.g., CeO 2 or the use of other mixed ionic/electronic perovskite materials like BaZr 0.1 Ce0.7Y 0.2−x Yb x O 3-δ (BZCYYb) or BaZr 0.4 Ce 0.4 Y 0.2O3−δ (BZCY), which can be oxygen ion or proton conductors (Wang et al, 2014;Chen et al, 2016). As for the case of carbon tolerance, CeO 2 supporting catalytic systems are characterized by the fast transition between Ce 4+ to Ce 3+ that provides highly mobile O species, which can oxidize adsorbed S species either on Ni or on CeO 2 .…”
Section: Sulfur Tolerance Of the Ni/gdc Niau/gdc And Niaumo/gdcmentioning
confidence: 99%
“…In addition to the modification of surface adsorption properties of Ni, significant sulfur tolerance resistance can be obtained by modifying the ionic oxide support e.g., CeO 2 or the use of other mixed ionic/electronic perovskite materials like BaZr 0.1 Ce0.7Y 0.2−x Yb x O 3-δ (BZCYYb) or BaZr 0.4 Ce 0.4 Y 0.2O3−δ (BZCY), which can be oxygen ion or proton conductors (Wang et al, 2014;Chen et al, 2016). As for the case of carbon tolerance, CeO 2 supporting catalytic systems are characterized by the fast transition between Ce 4+ to Ce 3+ that provides highly mobile O species, which can oxidize adsorbed S species either on Ni or on CeO 2 .…”
Section: Sulfur Tolerance Of the Ni/gdc Niau/gdc And Niaumo/gdcmentioning
confidence: 99%
“…Another important strategy for improving the coking/sulfur tolerance of Ni‐based anodes is to increase the gasification rate of deposited carbon/sulfur on the anode 21, 22, 23. In the oxygen‐ion‐conducting SOFCs, water is produced at the anode under current polarization, which can be used to remove the deposited carbon/sulfur on the anode.…”
mentioning
confidence: 99%
“…In a pioneering work, Liu and co‐workers reported that BaO nanoparticles deposited on Ni surface can adsorb water, facilitating the rapid removal of the deposited carbon/sulfur on the anode 21. More recently, Shao and co‐workers demonstrated that using a water‐storable proton conductor in a Ni‐based anode resulted in excellent coking/sulfur resistance 22, 23. However, the operational stability of this anode was unsatisfactory due to the large Ni particle size and poor contact between Ni and the water‐storable phase 23…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the study of SOFC fed with underground coal gasification (UCG) gas, a widely used hydrocarbon in China, Australia and India, is rarely reported [22,23]. And SOFC can convert chemical energy in the fuel directly to electricity with fuel flexibility, high efficiency, and low emissions of greenhouse gas such as CO 2 and environmental pollutants like NO x [25][26][27]. And SOFC can convert chemical energy in the fuel directly to electricity with fuel flexibility, high efficiency, and low emissions of greenhouse gas such as CO 2 and environmental pollutants like NO x [25][26][27].…”
Section: Introductionmentioning
confidence: 99%